Students at work on campus farm - News Bureau, California Polytechnic College, San Luis Obispo:::::::::
Two tractors, driven by students, move in parallel, with the tractor on the left cutting crop plants and then ejecting the cuttings into the truck on the left's tall wooden trailer.